Juridical Analysis Of The Mechanism Of Non-Conviction Based Asset Forfeiture In The Settlement Of Corruption Crimes - Farida Wulandari; Soerya Respationo; Erniyanti Erniyanti (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
Corruption is one of the major problems that hinder development and prosperity in Indonesia. In Batam City, the handling of corruption crimes is often not optimal, especially in the aspect of recovering illegally obtained assets. The Non-Conviction Based Asset Forfeiture (NCBAF) mechanism is one of the instruments that is expected to accelerate the process of recovering state losses without having to wait for criminal punishment. This research aims to assist in the regulation of NCBAF laws and standards in resolving corruption crimes in Batam City, as well as identify the obstacles faced and efforts that can be made to optimize their implementation. The research methods used are normative juridical and empirical juridical. The normative juridical approach is carried out by reviewing relevant regulations, including Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes, as well as related literature. The empirical juridical approach is carried out through case studies and interviews with law enforcement officials in Batam City. The results of the study show that although the NCBAF has been regulated in the regulations, its implementation in Batam City still faces various obstacles, such as lack of coordination between law enforcement agencies, high standards of proof, unclear legal procedures, and limited resources and technical capacity of the apparatus. Examples of corruption in infrastructure assistance, embezzlement of social funds, and corruption in the procurement of goods and services show that assets suspected of originating from criminal acts often cannot be immediately confiscated and utilized by the state. To overcome these obstacles, this study suggests increased coordination between law enforcement agencies through the formation of special teams, the preparation of clear standard operating procedures (SOPs), intensification of training for law enforcement officials, increased international cooperation, and community campaigns to increase public awareness and support. With these steps, the NCBAF is expected to become a more effective instrument in eradicating corruption and recovering state losses in Batam City.